Industry academia representatives gather in Roundtable Discussion RTD towards high level TVET - Mimi Rabita, Abdul Wahit (2023)
KUALA LUMPUR, 27 February 2023 - The holding of the academia-industry Round Table Discussion (RTD) provided an opportunity for more than 40 industry representatives to discuss the direction of the high-level TVET programmes to meet the country’s needs.